1998
DOI: 10.2169/internalmedicine.37.927
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Damage with Characteristic Apoptotic Hepatocytes by Ingestion of Aplysia kurodai, a Sea Hare.

Abstract: A case of acute liver damage by ingestion ofAplysia kurodai, a sea hare is reported. A 40-yearold man, complaining of vomiting and pyrexia after eating a sea hare, was admitted. Laboratory data showed mild liver damage with sustained elevations of aminotransferases. Microscopic findings in the liver biopsy specimen revealed characteristic apoptotic hepatocytes accompanied by mitotic hepatocytes. It is suggested that bioactive substances in the sea hare might induce such apoptosis of hepatocytes in the liver. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Both glands exude substances that have been shown to be toxic to cnidarians [1]. Probably these substances also caused severe damage of the liver of a 40-year-old man, who ate Aplysia kurodai Baba, 1937 [60]. By experimental studies it was shown that the repellent substance in the ink gland is a monomethyl ester of phycoerythrobilin and is derived from phycoerythrin from the consumed red algae [61].…”
Section: Discussionmentioning
confidence: 99%
“…Both glands exude substances that have been shown to be toxic to cnidarians [1]. Probably these substances also caused severe damage of the liver of a 40-year-old man, who ate Aplysia kurodai Baba, 1937 [60]. By experimental studies it was shown that the repellent substance in the ink gland is a monomethyl ester of phycoerythrobilin and is derived from phycoerythrin from the consumed red algae [61].…”
Section: Discussionmentioning
confidence: 99%
“…The apparent lack of a physical defense against marine predators appears to be balanced by a host of chemical defenses instead, comprised of an array of toxic compounds that have been isolated from various species of sea hares . Depending on the sea hare species and potentially the geographic location, sea hare toxicity cases in humans appear to be divided into 2 distinct presentations, the first consisting primarily of acute neurological disturbances and the second consisting of liver damage without neurological symptoms . Nausea was the only common symptom that accompanied all 6 human cases …”
Section: Discussionmentioning
confidence: 99%
“…All the patients recovered within 1 month after conservative treatment. Sakamoto et al reported a case of a man presenting with nausea, vomiting, and abrupt chilling 6 hours after eating 2 pieces of the sea hare Aplysia kurodai . He rapidly developed acute liver damage with characteristic histological findings presenting apoptosis of numerous hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced apoptotic rate (>1-5 cells/ 10 000 hepatocytes) occurs in many forms of disease (10). This is particularly so in acute liver failure (11), due to acute rejection (12), HBV (13), HCV (14), herpes simplex hepatitis (15), Wilson's disease (16), alcoholic hepatitis (17), autoimmune hepatitis (18), and toxic liver injury (19). Apoptotic hepatocytes in acute liver failure in humans have been identified through conventional histology and chromatin fracturing using the terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) technique (11,20).…”
mentioning
confidence: 99%